Pengaruh Prosedur Kredit, Tingkat Suku Bunga Dan Kualitas Pelayanan Kredit Terhadap Keputusan Mengambil Kredit Pada BCA KCP Pondok Timur Bekasi - Slamet Maryoso; Dian Indah Sari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Abstract: This study aims to determine the effect of credit procedures, interest rates and quality of credit services on credit decisions at BCA Bank, Pondok Timur Bekasi branch. The location of this research is BCA Bank, Pondok Timur Bekasi branch. The research sample consisted of 90 people. The sampling method used was purposive sampling. Multiple linear regression analysis was used to analyze the research data. The conclusions of this study include: 1. The credit procedure variable partially has a positive and significant effect on credit decisions at BCA, Pondok Timur Bekasi branch. 2. The interest rate variable has a significant and positive effect partially on credit decisions at BCA, Pondok Timur Bekasi branch. 3. The credit service quality variable has a positive and significant impact on credit decisions at BCA, Pondok Timur Bekasi branch. 4. The credit procedure variable, interest rate level, and quality of credit services simultaneously have a positive and significant impact on credit decisions at BCA, Pondok Timur Bekasi branch.